2021
DOI: 10.1302/0301-620x.103b6.bjj-2020-2096.r1
|View full text |Cite
|
Sign up to set email alerts
|

Excellent mid-term follow-up for a new 3D-printed cementless total knee arthroplasty

Abstract: Aims Cementless total knee arthroplasty (TKA) offers the potential for strong biological fixation compared with cemented TKA where fixation is achieved by the mechanical integration of the cement. Few mid-term results are available for newer cementless TKA designs, which have used additive manufacturing (3D printing). The aim of this study was to present mid-term clinical outcomes and implant survivorship of the cementless Stryker Triathlon Tritanium TKA. Methods This was a single institution registry review o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 32 publications
3
18
0
Order By: Relevance
“…Additionally, all evaluated clinical and patient reported outcome scores including AKSS, OKS, KOOS and EQ5D showed significant improvements within the FU when compared to the preoperatively assessed values. Similar results were retrieved by other authors, who also reported a significant improvement of PROMS after cementless TKA [ 26 ].…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, all evaluated clinical and patient reported outcome scores including AKSS, OKS, KOOS and EQ5D showed significant improvements within the FU when compared to the preoperatively assessed values. Similar results were retrieved by other authors, who also reported a significant improvement of PROMS after cementless TKA [ 26 ].…”
Section: Discussionsupporting
confidence: 90%
“…The tibial pegs served as an extension of the limited bone fixation, which became an additional stressor from the lack of even bone ongrowth. Another possible mechanism leading to component fatigue failure can be instability/subluxation, which has been documented in several studies during short- to mid-term follow-up [ 5 , 6 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Long-term survivorship and outcome studies specific to a cementless highly porous titanium tibial baseplate are limited with the largest follow-up study currently reporting 5-year follow-up data on 228 patients [ 5 , 7 ]. No implant fractures of this design have been reported in these short-term to mid-term follow-up studies [ 5 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the thin form factor and batteryless feature, these force stickers would be apt candidates to enable smart force-sensitive implants. Today, the field of medical orthopedic implants is already looking to engineering fields for innovation, with personalized 3-D printed implants making a lot of headway [13][14][15]. The implants can be made much smarter by adding these force stickers on top of these 3-d printed structures; since these are highly flexible, the sticker would conform well to the implant's irregular personalized shape and be able to measure the bone joint forces as shown in Figure 2(b).…”
Section: Need For Batteryless and Sticker-like Force Sensorsmentioning
confidence: 99%